Percutaneous management of complicated parapneumonic effusion and empyema after surgical tube thoracostomy failure in children: a retrospective study - Ciftci, Turkmen Turan; Akinci, Devrim; Unal, Emre; Tanir, Gonul; Artas, Hakan; Akhan, Okan (Turkish Soc Radiology, 2021)
PURPOSE We aimed to evaluate the results of percutaneous management of complicated parapneumonic effusions (PPE) and empyema after surgical tube thoracostomy failure in children. METHODS A total of 84 children treated percutaneously after surgical tube thoracostomy failure between 2004 and 2019 were included to this retrospective study. Technical success was defined as appropriate placement of the drainage catheter. Clinical success was defined as complete resolution of infection both clinically and radiologically. Management protocol included imaging-guided pigtail catheter insertion, fibrinolytic therapy, serial ultrasonographic evaluation, catheter manipulations as necessary (revision, exchange, or upsizing), and appropriate antibiotherapy. All patients were followed up at least 6 months. RESULTS Technical success rate was 100%. Unilateral single, unilateral double, and bilateral catheter insertions were performed in 73, 9, and 2 patients, respectively. Inserted catheter sizes ranged from 8 F to 16 F. Streptokinase, urokinase, and tissue plasminogen activator were used as fibrinolytic agent in 29 (34%), 14 (17%), and 41 (49%) patients, respectively. In order to maintain effective drainage, 42 additional procedures (catheter exchange, revision, reposition, or additional catheter placement) were performed in 20 patients (24%). Clinical success was achieved in 83 of 84 patients (99%). Median catheter duration was 8 days (4-32 days). Median hospital stay during percutaneous management was 11.5 days (7-45 days). Factors affecting the median catheter duration were the presence of necrotizing pneumonia (p < 0.001) and bronchopleural fistulae (p < 0.001). CONCLUSION Percutaneous imaging-guided catheterization with fibrinolytic therapy should be the method of choice in pediatric complicated PPE and empyema patients with surgical tube thoracostomy failure. Percutaneous treatment is useful in avoiding more aggressive surgical options.
Keywords: Intrapleural Streptokinase; Necrotizing Pneumonia; Catheter Drainage; Collections